2019
DOI: 10.1002/pon.5239
|View full text |Cite
|
Sign up to set email alerts
|

Screening for post‐traumatic stress disorders in 1017 cancer patients and correlation with anxiety, depression, and distress

Abstract: ObjectivePost‐traumatic stress disorder (PTSD) is a severe psychiatric disorder, which might develop after a traumatic event, like cancer diagnosis, and threatens the patient's psychological and/or physiological integrity. Anxiety, depression, and mental distress are known to be common in cancer patients; however, the frequency of PTSD was not investigated thoroughly in this patient group so far. Here, we aim to screen cancer patients for PTSD symptoms and determine a possible correlation with anxiety, depress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…Also considering anxiety and depression, no data on cancer patients during the COVID-19 pandemic are available yet. However, if we compare the present cohort with historical cohorts of patients diagnosed with lymphoproliferative neoplasms, we can state that levels of HADS found in our study are significantly higher on both the depression subscale and on the general scale (24).…”
Section: Discussionmentioning
confidence: 58%
“…Also considering anxiety and depression, no data on cancer patients during the COVID-19 pandemic are available yet. However, if we compare the present cohort with historical cohorts of patients diagnosed with lymphoproliferative neoplasms, we can state that levels of HADS found in our study are significantly higher on both the depression subscale and on the general scale (24).…”
Section: Discussionmentioning
confidence: 58%
“…Numerous studies documented that female patients suffered more from anxiety and depression during their cancer experience and had a poorer quality of life than men. [46][47][48][49] In addition, Martínez et al 50 reported that 25% of breast cancer patients reported clinical distress.…”
Section: Women Scored Higher On Anxiety and Depressionmentioning
confidence: 99%
“…Depression and anxiety are more frequent in cancer patients than in persons without a chronic health condition, but prevalence rates vary widely between studies. In cancer patients, estimated prevalence rates range between 11% and 57% for depression, and between 6.5% and 23% for anxiety 9–11 . Anxiety disorders often present in association with depression 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Anxiety disorders often present in association with depression 12 . Furthermore, a recent study in a large sample of cancer patients reported significant correlations of PTSD symptoms with both, depression and anxiety 11 …”
Section: Introductionmentioning
confidence: 99%